First‐ and second‐trimester maternal serum markers of pre‐eclampsia in twin pregnancy. (May 2016) - Svirsky, R.; Levinsohn‐Tavor, O.; Feldman, N.; Klog, E.; Cuckle, H.; Maymon, R.
ABSTRACT: Objective: To evaluate the distribution of first‐ and second‐trimester maternal serum markers in twin pregnancy with and without pre‐eclampsia. Methods: One‐hundred and forty‐four twin and 109 unaffected singleton pregnancies were recruited from the same institution. First‐ and second‐trimester maternal blood samples were stored and measured retrospectively for serum placental growth factor (PlGF), pregnancy‐associated plasma protein‐A (PAPP‐A), free β ‐human chorionic gonadotropin ( β ‐hCG) and α ‐fetoprotein (AFP). All had measurement of first‐trimester serum markers, and 167 (66%) had second‐trimester tests. Values were expressed in multiples of the gestation‐specific median (MoMs) in singletons, adjusted for maternal weight, as appropriate. Results: Pre‐eclampsia was diagnosed in 12 (9.0%) twin pregnancies of 133 continuing beyond 22 weeks. In unaffected twin pregnancies, all serum markers were statistically significantly increased ( P < 0.0001), consistent with a doubling of concentration. Among twin pregnancies, those with pre‐eclampsia had a significantly reduced median PlGF compared with surviving unaffected twin pregnancies (0.96 MoM vs 1.46 MoM; P < 0.0002, two‐tailed), whilst median PAPP‐A, which is known to be reduced in affected singleton pregnancies, was increased (3.91 MoM vs 2.43 MoM; P < 0.0005, two‐tailed). The levels of free β ‐hCG ( P < 0.02) and AFP ( P < 0.05) were also significantly raised, but to a lesser extent than was the level of PAPP‐A. Using a logistic regression algorithm based on first‐ and second‐trimester PlGF and PAPP‐A, together with previously published uterine artery Doppler and mean arterial pressure measurements in the same series, the predicted pre‐eclampsia detection rate was 65% for a 10% false‐positive rate. Conclusions: In twin pregnancy, the predicted detection rate of pre‐eclampsia using first‐ and second‐trimester maternal serum and biophysical markers is good. In contrast to singleton pregnancy, PAPP‐A levels are raised in the first trimester of twin pregnancies destined to develop pre‐eclampsia and therefore a different prediction algorithm is needed. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.